Students’ Readiness and Problems to Face Online Learning in Pandemic Era - Meladina Meladina; Hermi Zaswita (Tamaddun Life, 2020)
The pandemic era has changed many aspects of the community lifestyle. It also includes the English teaching and learning process. Many teachers and students have to do teaching and learning online. They find some difficulties problems during that process. This research aimed to find out the Students' Readiness and problems to face online learning in Pandemic Era. It was qualitative research which was conducted at Fort De Kock University from July to October 2020. The population was all of the students who learn English at Fort De Kock University. Using a purposive sampling technique, the nursing and physiotherapy students in the third and fifth semesters were chosen as the samples. The data were taken from the questioner and in-depth interviews. Then, they were analyzed by computerization and transcription. This research found that most of the students had difficulties joining online learning such as signal, internet budget, lack of understanding and focus, and the interactions. By analyzing the results of this research, it can be concluded that the students are not ready to face online learning. It is suggested to the stakeholder to be more creative and innovative to face those problems.